Contribution to the Molecular Phylogeny of Anthribidae (Coleoptera: Curculioniodea) Inferred from COI Sequences - Ali Nafiz Ekiz; Polen Döngel (Journal of Advanced Research in Natural and Applied Sciences)
Fungus weevils, Anthribidae, is a relatively small family, including about 3861 species worldwide, of the diverse superfamily Curculioniodea. Currently, three subfamilies are recognized within Anthribidae (Anthribinae, Choraginae and Urodontinae); however, this subfamily division is somewhat controversial and not accepted by all authors of the field. In this study, we constructed family level evolutionary histories within Anthribidae by using COI sequences and discussed the phylogenetic relations between these three subfamilies and also between tribes. Estimates of evolutionary divergence between sequences used in this study are calculated and the overall average divergence was 0,274 where minimum was 0,133 and maximum was 0,365. Phylogenetic and evolutionary histories were inferred by using 34 COI sequences representing most of the tribes and subfamilies currently recognized within Anthribidae. The phylogenetic trees were inferred by using Neighbor-Joining (NJ) and Maximum Likelihood (ML) methods. Both method provided quite similar evolutionary histories. According to the phylogenetic trees, Anthribinae + Coraginae members together constitute a monophyletic clade, which makes currently recognized Anthribinae paraphyletic and Coraginae polyphyletic. Urodontinae seems to form a monophyletic clade with respect to used COI sequences. Tribal classification which fully seem to depends on morphological characters are useful for practical taxonomic purposes but most tribes (those represented with more than one species/sequence) does not constitute monophyletic clades.